In Vitro Efficacy of Flomoxef against Extended-Spectrum Beta-Lactamase-Producing Escherichia coli and Klebsiella pneumoniae Associated with Urinary Tract Infections in Malaysia - Soo Tein Ngoi; Cindy Shuan Ju Teh; Chun Wie Chong; Kartini Abdul Jabar; Shiang Chiet Tan; Lean Huat Yu; Kin Chong Leong; Loong Hua Tee; Sazaly AbuBakar (MDPI AG, 2021)
The increasing prevalence of extended-spectrum β-lactamase (ESBL)-producing Enterobacteriaceae has greatly affected the clinical efficacy of β-lactam antibiotics in the management of urinary tract infections (UTIs). The limited treatment options have resulted in the increased use of carbapenem. However, flomoxef could be a potential carbapenem-sparing strategy for UTIs caused by ESBL-producers. Here, we compared the in vitro susceptibility of UTI-associated ESBL-producers to flomoxef and established β-lactam antibiotics. Fifty Escherichia coli and Klebsiella pneumoniae strains isolated from urine samples were subjected to broth microdilution assay, and the presence of ESBL genes was detected by polymerase chain reactions. High rates of resistance to amoxicillin-clavulanate (76-80%), ticarcillin-clavulanate (58-76%), and piperacillin-tazobactam (48-50%) were observed, indicated by high minimum inhibitory concentration (MIC) values (32 µg/mL to 128 µg/mL) for both species. The ESBL genes blaCTX-M and blaTEM were detected in both E. coli (58% and 54%, respectively) and K. pneumoniae (88% and 74%, respectively), whereas blaSHV was found only in K. pneumoniae (94%). Carbapenems remained as the most effective antibiotics against ESBL-producing E. coli and K. pneumoniae associated with UTIs, followed by flomoxef and cephamycins. In conclusion, flomoxef may be a potential alternative to carbapenem for UTIs caused by ESBL-producers in Malaysia.